PENGARUH STATUS SOSIAL EKONOMI ORANG TUA TERHADAP PERILAKU KONSUMSI SELAMA COVID-19 PADA MAHASISWA PENDIDIKAN EKONOMI FKIP UNTAN - Harianto Harianto; Bambang Genjik Sumartono; Jumardi Budiman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractThis study aims to (1) determine the socioeconomic conditions of parents duringthe Covid-19 pandemic. (2) Knowing the consumption behavior of economiceducation students during the Covid-19 pandemic. (3) Knowing the influence ofparents' socioeconomic status on students' consumption behavior during the Covid-19 pandemic. In this study using a quantitative approach. Collecting data in thisstudy using a questionnaire with a random sampling technique with a sample of135 respondents. Data collection techniques used are indirect communication anddocumentary studies. Analysis of the data used is simple linear regression analysis.Based on this research, it shows (1) the socioeconomic conditions of parentsduring the Covid-19 pandemic are in the sufficient category with a proportion of44.49% (2) Consumptive behavior of students during the Covid-19 pandemic isseen in the high category with a proportion of 77.63% (3) The effect of parents'socioeconomic status on consumption behavior during the Covid-19 pandemic oneconomic education students FKIP UNTAN whose simple linear regression resultsare known to have a t count < from t table (-1,497 < 1,977) and a significance <0.05 (0 0.05 < 0.137), then Ha is rejected and H0 is accepted, and the result of thecoefficient of determination (R2) is 0.097.Keywords: The Socioconomics Status Of Parent, Konsumtive Behavior, PandemiCovid-19